Mine waste: The unseen dead in a mining landscape. (October 2018) - Esterhuysen, Amanda; Knight, Jasper; Keartland, Tarquin
Mined landscapes represent the exploitation of Earth's resources, but they also provide evidence for the unequal power relations and changing attitudes to resource use (including both geology and human beings as resources) within mining communities and their surrounding political and economic contexts. This study explores the impacts that gold mining has had on the landscapes of Johannesburg, South Africa, with particular reference to how land used for Black mineworkers' cemeteries was reclaimed and used to store mine waste. The study describes how the uncovering of an early 20th century cemetery site beneath a mine waste dump poses questions on the meaning and significance of the dead in the urban industrial landscape. The deliberate burial and then accidental rediscovery of these bodies some 100 years later is a significant metaphor for the reinterpretation of racialised urban landscapes in South Africa.